운동부하 검사상 무증상 심근 허혈 환자의 관동맥 병변 소견 - 조인종; In Jong Cho; 서정평; Jung Pyung Suh; 류문희; Moon Hee Rheu; 이명곤; Myung Kon Lee; 박종수; Jong Soo Park; 박주형; Joo Hyung Park; et al. (The Korean journal of medicine, 1994)
Objectives: Silent myocardial ischemia is defined as the presence of transient ischemic alterations in absence of angina or its equivalents. In recent reports, silent ischemia comprises about 60-80% of total ischemic events in patients with symptomatic angina and its prognosis is similar to typical painful angina, So, we studied to compare the difference of coronary angiographic features between painful angina and silent angina in patients with positive treadmill exercise test. Method: We studied retrospectively coronary angiographic features of 34 patients; 20 patients with painful treadmill exercise test were grouped in A and 14 patients without pain were grouped in B. Both groups were positive in Thallium corynary perfusion scan. Results: 1) There were no significant differences in sex, age, smoking and hypertension between group A and B but diabetes were more prevalent in group A than in B(p< 0,05) 2) Total exercise duration, ST segment deviation and rate pressure product were not different between two groups in treadmill exercise test. Although treadmill score was significantly low in group A (p<0.05), there was no singificant difference between two groups in case of subtracting treadmill angina index from treadmill score. 3) In dipyridamole Tl scan, defect volume ratio was not different in two groups although defect index was significantly greater in group A(p<0.05). 4) In coronary angiographic findings, there were no sigificant differences in number of stenosed vessels, left ventricular ejection fraction and left ventricular end diastolic pressure, but right coronary artery lesion is more common in group A than group B(p<0,05). 5) The most common clinical diagnosis of studied subject was unstable angina, But there were no statistically difference between two groups. Conclusion: This results suggest that patient with silent myocardial ischemia has similar coronary artery disease to those with painful myocardial ischemia, Early detection and treatment of silent ischemia is essential in the management of ischemic teart disease.